1982
DOI: 10.1068/p110541
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Constraints on Apparent Rotational Movement

Abstract: Abstract. The visual illusion of apparent rigid rotation was produced by sequential alternation of two views of the same object in different orientations. The minimum stimulus-onset asynchrony required for the appearance of rigid rotation was a linearly increasing function of the angular difference in orientation between the two views. Variation in the size of the object affected the zero-intercept of the function, but the slope was virtually constant. The slope invariance suggests that the appearance of rigid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
14
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
6
14
0
Order By: Relevance
“…According to Cavanagh and Mather, similar comparator mechanisms underlie both types of motion perception. The observation in Experiment 1, which indicated that apparent motion between complementary images yields a relationship between SOA and angular deviation that is the same as that found for intact or complete images (e.g., Farrell et al, 1982;Shepard & Judd, 1976), is consistent with this view. The results also suggest that image-based and object-based apparent motion share the same mode of operation.…”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…According to Cavanagh and Mather, similar comparator mechanisms underlie both types of motion perception. The observation in Experiment 1, which indicated that apparent motion between complementary images yields a relationship between SOA and angular deviation that is the same as that found for intact or complete images (e.g., Farrell et al, 1982;Shepard & Judd, 1976), is consistent with this view. The results also suggest that image-based and object-based apparent motion share the same mode of operation.…”
Section: Methodssupporting
confidence: 77%
“…Under suitable conditions, alternating static images that are related by a shape-preserving similarity transformation produce the perception of a rigid motion over a specific trajectory. A minimum temporal separation between the two images is required for such motion, and this minimum increases linearly as a function of the spatial separation between them (Bundesen, Larsen, & Farrell, 1983;Farrell, 1983;Farrell, Larsen, & Bundesen, 1982;Farrell & Shepard, 1981;Korte, 1915;Shepard & Judd, 1976). It is generally assumed that the intercept of this function measures the time it takes to encode the two successive stimuli as different views of the same object, and that the slope reflects the maximum speed of interpolating a path between them (McBeath & Shepard, 1989;Shepard, 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A display for which kinematic geometry prescribes a more curved, longer path of transformation should therefore require a longer SOA and hence (for a fixed stimulus duration) a longer lSI. If SOA is too short for completion of the circular path, the perceptual system may connect the alternately displayed stimuli through a path that is flattened and hence shortened enough to allow motion to be completed within the time available (as suggested, also, by the results of Farrell et al, 1982;Proffitt et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, this is because more time is needed for the impletion of a longer path. Indeed, the increase tends to be linear, whether the motion itself is rectilinear (Corbin, 1942;see Shepard, 1984, p. 421) or rotational (Bundesen et al, 1983;Farrell, 1983;Farrell, Larsen, & Bundesen, 1982;Farrell & Shepard, 1981;Shepard & Judd, 1916). Moreover, Shepard and Zare (1983), using a new technique of "pathguided" apparent motion, demonstrated that even when the straight distance between two alternately presented dots was fixed, the critical SOA for apparent motion over an experimenter-determined curved path increased linearly with the length of that curved path.…”
mentioning
confidence: 99%